Esophageal substitutions in children. - Pedro A. Vilorio Barreras (Medisur)
Esophageal replacements in children usually are necessary in patients with of esophageal atresia or those develop inflammatory scars after consumption of caustic substances. For the substitutive procedure diverse organs are employed, like small or thick intestine and stomach. We presented the Good Clinical Practices Guideline for Esophageal replacement, approved by consensus in the the 3th National Good Clinical Practices Workshop in Pediatric Surgery (Camagüey, Cuba; February 23 - 26, 2004).